Search for lepton-flavor-violating $${τ }^{-}→ {{\ell}}^{-}{K}_{s}^{0}$$ decays at Belle and Belle II - The Belle and Belle II collaborations; I. Adachi; L. Aggarwal; H. Ahmed; Y. Ahn; H. Aihara; N. Akopov; S. Alghamdi; M. Alhakami; A. Aloisio; N. Althubiti; K. Amos; et al. (Journal of High Energy Physics)
Abstract We present the results of a search for charged-lepton-flavor violating decays $${τ }^{-}→ {{\ell}}^{-}{K}_{s}^{0}$$ , where ℓ − is either an electron or a muon. We combine e + e − data samples recorded by the Belle II experiment at the SuperKEKB collider (428 fb −1) with samples recorded by the Belle experiment at the KEKB collider (980 fb −1) to obtain a sample of 1.3 billion e + e − → τ + τ − events. We observe 0 and 1 events and set 90% confidence level upper limits of 0.8 × 10 −8 and 1.2 × 10 −8 on the branching fractions of the decay modes $${τ }^{-}→ {e}^{-}{K}_{S}^{0}$$ and $${τ }^{-}→ {μ }^{-}{K}_{S}^{0}$$ , respectively. These are the most stringent upper limits to date.